We will be champions: Leaders' confidence in 'us' inspires team members' team confidence and performance - Fransen, K.; Steffens, N. K.; Haslam, S. A.; Vanbeselaere, N.; Vande Broek, G.; Boen, F. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The present research examines the impact of leaders' confidence in their team on the team confidence and performance of their teammates. In an experiment involving newly assembled soccer teams, we manipulated the team confidence expressed by the team leader (high vs neutral vs low) and assessed team members' responses and performance as they unfolded during a competition (i.e., in a first baseline session and a second test session). Our findings pointed to team confidence contagion such that when the leader had expressed high (rather than neutral or low) team confidence, team members perceived their team to be more efficacious and were more confident in the team's ability to win. Moreover, leaders' team confidence affected individual and team performance such that teams led by a highly confident leader performed better than those led by a less confident leader. Finally, the results supported a hypothesized mediational model in showing that the effect of leaders' confidence on team members' team confidence and performance was mediated by the leader's perceived identity leadership and members' team identification. In conclusion, the findings of this experiment suggest that leaders' team confidence can enhance members' team confidence and performance by fostering members' identification with the team.